Assessment varieties garden pea (Pisum sativum L.) in terms of quality green peas and seeds - В. М. Стригун (Plant Varieties Studying and Protection)
To obtain a high-quality source material for breeding new varieties of garden pea studied biochemical and technological properties of 450 sample grades collection. As a result, selected varieties, sources that had green peas in a high content of individual chemicals and combine incorporates several of these substances. These varieties have different duration of the growing season. Among them, identified those with green peas excessive ripeness not for a long time. Such quality varieties are especially important because provides over a longer period of receipt of a high quality green peas in a cannery. In addition, the collection highlighted garden pea varieties of high quality seed in biological maturity. The selected varieties were included in the selection process and, based on a number of new varieties garden pea, providing conveyor receipt green peas for processing plants.